Short term effects of annual ryegrass, red clover and hairy vetch cover crops on various indicators of soil health - Stout, Breanna (Kansas State University, 2014)
The world’s population has passed 7 billion and is expected grow to more alarming numbers by the year 2050. The increase in human life on the planet ushers the need to responsibly and sustainably grow more food. In order to meet the demand necessary, it is crucial that soil remains healthy and crop yields continue to increase in efficiency. Irresponsible or ill-informed practices can lead to depleted resources and degradation of fertile soils that may limit a producers’ ability to sustainably grow food. Cover crops are a tool that can be used to address issues the modern producer may face. Cover crops have been shown to increase cash crop productivity, improve soil health by improving soil physical and chemical properties as well as providing protection from soil erosion runoff or nutrient leaching. A study was conducted in 2014 to examine the short term effects associated with cover cropping systems. The effects of ryegrass, red clover and a cover crop cocktail (mixture of ryegrass, red clover and hairy vetch) compared to bare tilled and bare control plots were studied. The five treatments were replicated three times in a completely randomized study and analyzed. Soil physical health indicators such as bulk density and porosity were calculated. Soil and cover crop nutrient use, as well as, soil moisture content data was collected and analyzed using excel and ANOVA statistical procedures. In the short term, the study found that there was only statistically significant differences between cover cropping regimens, tilled and control plots in regards to biomass production and biomass nutrient concentrations (α=0.05). The cocktail mix provided more biomass, N and P than the ryegrass and clover plots alone. Observable differences in cover crop volumetric soil moisture and water used between plots demonstrated that cover crops utilize soil moisture in the short term, which must be considered in areas experiencing water stress. Although more long-term data is needed to truly quantify how cover crops effect various aspects of soil health, this study demonstrated how cover crops have the potential for providing numerous benefits such as increased erosion control, lower reliance on anthropogenically created nutrients and the reduction of weeds. Overall the benefits associated with cover crops are still being researched and while adoption of cover cropping systems has been slow, a push towards agricultural sustainability while increasing food production will increase the amount of producers utilizing cover crops in the coming years.
Keywords: Cover crops; Agriculture; Soil moisture; Soil healthCover crop cocktail; Environmental Engineering (0775)